OVERVIEW ON METHODS OF SYNTHESIS OF NANOPARTICLES - PATIL, NILESH; BHASKAR, RAJVEER; VYAVHARE, VISHAL; DHADGE, RAHUL; KHAIRE, VAISHNAVI; PATIL, YOGESH (International Journal of Current Pharmaceutical Research, 2021)
In recent years, interest in the development of novel drug delivery systems using nanoparticles has gained more attention. The nanoparticles offer several advantages over other conventional drug delivery systems. Nanoparticles have gained importance in technological advancements due to their modifiable physical, chemical and biological properties with improved performance over their bulk foils. Nanoparticles can simply move in the body due to their small size and reach very complex organs through diverse routes. The high stability, controlled drug release makes nanoparticles the most suitable drug delivery system. Along with all these advantages, they offer variety in routes of administration. Both hydrophilic, as well as hydrophobic drugs, can be delivered in the form of nanoparticles. Nanoparticles have been used as a physical approach to modify and advance the pharmacokinetics and pharmacodynamics possessions of various types of drug molecules. Thesol-gel technique is a stress-free and very inexpensive process to formulate metal oxides and permits control over the doping process or adding of transition metals, as related to other research techniques. The study of different methods of synthesis of nanoparticles is essential to obtain desired nanoparticles with specific sizes and shapes. They are suitable candidates for various marketable and local applications, which include imaging, catalysis medical applications and environmental applications. This review mainly focuses on approaches used for the production of nanoparticles and different methods of synthesis of nanoparticles such as physical, chemical and biological method.